2016
DOI: 10.1016/j.indcrop.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

High performance waste-derived filler/carbon black reinforced guayule natural rubber composites

Abstract: Guayule rubber (GNR) is an alternative source of natural rubber that does not crossreact with Type I latex allergy because it does not contain any proteins which can be recognized by antibodies raised against Hevea brasiliensis allergens. To advance the commercialization of this elastomer and diversify sources of natural rubber, efficient reinforcement of GNR is required to match the physical properties of vulcanized materials made from Hevea natural rubber in specific products. Superior or comparable reinforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Applying this concept can prevent the problem of the increasing amount of waste rubber, which presents as an added difficulty the existence of a three-dimensional cross-linked structure that makes it more difficult for further processing and recycling [21].Taking into account the advantages of the use of waste fillers (cellulose/lignocellulose-based fillers and GTR), a new strategy to improve the performance properties of biocomposites was considered in this study. Instead of applying the fillers individually, the mixture of chosen fillers can be introduced into the system The application of hybrid fillers [22][23][24] may cause the occurrence of synergistic effects, providing superior results in terms of performance than the sum of the effects for the separate filler [25,26].However, not only modification, ratio, and type of rubber matrix and fillers have a significant influence on the performance properties of rubber biocomposites. In the fabrication of elastomers, vulcanization can be used to bond the fillers to the matrix, obtaining an improvement of the properties due to a good integration of the disperse particles into the whole material.…”
mentioning
confidence: 99%
“…Applying this concept can prevent the problem of the increasing amount of waste rubber, which presents as an added difficulty the existence of a three-dimensional cross-linked structure that makes it more difficult for further processing and recycling [21].Taking into account the advantages of the use of waste fillers (cellulose/lignocellulose-based fillers and GTR), a new strategy to improve the performance properties of biocomposites was considered in this study. Instead of applying the fillers individually, the mixture of chosen fillers can be introduced into the system The application of hybrid fillers [22][23][24] may cause the occurrence of synergistic effects, providing superior results in terms of performance than the sum of the effects for the separate filler [25,26].However, not only modification, ratio, and type of rubber matrix and fillers have a significant influence on the performance properties of rubber biocomposites. In the fabrication of elastomers, vulcanization can be used to bond the fillers to the matrix, obtaining an improvement of the properties due to a good integration of the disperse particles into the whole material.…”
mentioning
confidence: 99%
“…7 Of particular interest are those biofillers, which serve as multifunctional additives. Barrera and Cornish 12,13 studied the effect of waste-derived fillers as co-fillers for carbon black (CB) and found that eggshell particles increased the rate of cure, which resulted in higher crosslink density and improved mechanical properties. Procho n and Ntumba 9 added hydrolysates of cattle hair keratin and bird feather wastes to carboxylated nitrile rubber (XNBR) and the composite mechanical properties and oil resistance were improved, while surface abrasion was reduced.…”
Section: Introductionmentioning
confidence: 99%
“…A white rice husk ash filler was investigated as a reinforcing filler by Da Costa et al 10,11 and found to function in a catalytic capacity, accelerating the crosslinking reaction and lowering activation energy (E a ). Barrera and Cornish 12,13 studied the effect of waste-derived fillers as co-fillers for carbon black (CB) and found that eggshell particles increased the rate of cure, which resulted in higher crosslink density and improved mechanical properties. When commercial proteins were added to guayule rubber (GR), Lhamo and McMahan 14 found that the composite green strength, bulk viscosity, and thermo-oxidative stability were improved.…”
Section: Introductionmentioning
confidence: 99%
“…In the rubber industry, in order to improve mechanical properties of the materials and get cost reduction, fillers such as carbon black (CB) and calcium carbonate (CaCO 3 ) are usually employed owing to the excellent reinforcing characteristics and low cost, respectively . However, the possibility of obtaining various colors like red would be lost if the CB filler was introduced, and the excessive amount of CaCO 3 was not favorable to the mechanical performance of polymers .…”
Section: Introductionmentioning
confidence: 99%